Pierre Gourou, du pessimisme tropical à l’optimisme raisonné… - Jean-Pierre Raison (Confins)
The analysis of the thought of Pierre Gourou on the tropical world during his long career reveals a significant change from the pessimism of the early years, where he was still marked by his work on high densities of Asian deltas, to the last, where he showed some optimism when the mode was rather to see the Third World “in trouble”. Great geographer, but certainly not the “father” of a “tropicalist” school in France, Pierre Gourou, free spirit, was primarily a cheerful geographer.